Treatment of Cheyne‐Stokes Respiration Reduces Arrhythmic Events in Chronic Heart Failure. (11th July 2013) - Bitter, Thomas; Gutleben, Klaus‐Jürgen; Nölker, Georg; Westerheide, Nina; Prinz, Christian; Dimitriadis, Zisis; Horstkotte, Dieter; Vogt, Jürgen; Oldenburg, Olaf
Cheyne‐Stokes Respiration and Arrhythmias Objective This study aimed to investigate whether adequate treatment of Cheyne‐Stokes respiration (CSR) reduces the risk of arrhythmic events in patients with chronic heart failure (CHF). Methods A cohort of 403 registry patients with CHF (LVEF≤45%, NYHA‐class≥2) and implanted cardioverter‐defibrillator devices (ICD) was studied. They underwent overnight polygraphy, with 221 having mild or no CSR (apnea‐hypopnea index [AHI]<15/h), and 182 having moderate to severe CSR (AHI>15/h). Latter ones were offered therapy with adaptive servoventilation (ASV), which 96 patients accepted and 86 rejected. During follow‐up (21± 15 months) defibrillator therapies were recorded in addition to clinical and physiologic measures of heart failure severity. Results Event‐free survival from (a) appropriate cardioverter‐defibrillator therapies and (b) appropriately monitored ventricular arrhythmias was shorter in the untreated CSR group compared to the treated CSR and the no CSR group. Stepwise Cox proportional hazard regression analysis showed untreated CSR (a: hazard ratio [HR] 1.99, 95% confidence interval [CI] 1.46–2.72, P < 0.001; b: HR 2.19, 95%CI 1.42–3.37, P < 0.001), but not treated CSR (a: HR 1.06, 95%CI 0.74–1.50; P = 0.77; b: HR 1.21, 95%CI 0.75–1.93, P = 0.43) was an independent risk factor. The treated CSR group showed improvements in cardiac function and respiratory stability compared to the untreated CSR group. Conclusion This study demonstrates a decrease of appropriate defibrillator therapies by ASV treated CSR in patients with CHF and ICD. A reduced exposure to hyperventilation, hypoxia, and improvement in indices of CHF severity and neurohumoral disarrangements are potential causative mechanisms.